Reliability-based analysis of engineering structures - Ang, Kevin Boon Hwee (Nanyang Technological University, 2021)
Traditional safety factor method is unsuitable for complex structures in the physical world. This method only acts as a design approximation to compensate the inevitable uncertainties which may consequently lead to a design failure or an expensive design. Thus, the Reliability-Based Approach (RBA) is introduced to be more reliable than the former approach. The RBA utilizes statistical means to assess the probability of failure of a structural design. This modern insight enables engineers to forecast the probabilistic design based on input parameters. Furthermore, with the aid of ANSYS, multiple input design parameters can be simulated and analysed simultaneously to produce meaningful output results within a brief period of time. In short, RBA allows engineers to balance the cost and practicality of an engineering design in an efficient manner.This project focuses on RBA in analysing real-life engineering structure using ANSYS. The purpose of this research is to validate the credibility of reliability-based analysis as compared to the traditional safety factor method. For all the following simulations carried out in this project, constant design parameters are selected, and the Latin Hypercube Sampling technique will be executed within a specific sample size. This report highlights the overview usage of ANSYS and RBA on 2 engineering structures: cantilever I-beam and crane hook. The results of it will comprise static structural analysis and probability of failure.